Correspondence and engrave portrait of Alexander Scammell - Scammell, Alexander, 1747-1781.
ALS (undated) written by Scammell to his brother, Samuel Scammell, expressing his disappointment in teaching school and his desire to be apprenticed to his brother as a physician; ALS (1781 March 7) written by Scammell as a Continental Army officer to an unknown recipient regarding the poor quality of clothing and boots issued to his troops; ALS (1824 October 11) written by Scammell's nephew, John Scammell, to John Brazer Davis relating to his uncle's early life; and an engraved portrait of Alexander Scammell.
Teacher, surveyor, and Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Davis, John Brazer, -- 1798-1832 -- Correspondence; Scammell, John -- Correspondence; Scammell, Samuel -- Correspondence; United States. -- Continental Army -- Uniforms; Apprentices; Physicians; Teachers -- United States -- Attitudes; United States -- History -- Revolution, 1775-1783.; Army officers; Educators; Surveyors